Adsorptive granulocyte and monocyte apheresis: A potentially relevant therapeutic option for COVID-19. (October 2020) - Kanekura, Takuro; Kawahara, Koichi
Highlights: Cytokine storm and thromboembolism are major problems in patients with coronavirus disease 2019 (COVID-19). Adsorptive granulocyte monocyte apheresis (GMA) is an extracorporeal treatment. GMA selectively depletes elevated and activated myeloid lineage cells. GMA decreases proinflammatory cytokines and neutrophil–platelet aggregates. GMA could be a potentially relevant therapeutic option for COVID-19. Abstract: The overproduction of proinflammatory cytokines and subsequent thromboembolism are major problems of coronavirus disease 2019 (COVID-19). Adsorptive granulocyte and monocyte apheresis (GMA), used for ulcerative colitis, is an extracorporeal therapy designed to remove activated myeloid lineage cells. Previous studies have demonstrated that GMA decreases proinflammatory cytokines and neutrophil–platelet aggregates. The effect of GMA on COVID-19 in a patient with ulcerative colitis was recently reported. The modes of action of GMA together with the findings of this case report indicate that GMA could be a relevant treatment option for COVID-19.